Water and Membrane Dynamics in Suspensions of Lipid Vesicles Functionalized with Poly(ethylene glycol)s - Clop, Eduardo Matias (2014)
The present work was aimed at studying the molecular dynamics at different levels of model membranes having a simulated glycoclix, with focus on the molecular crowding conditions at the lipid–water interfacial region. Thus, binary mixtures of dipalmitoylphosphatidylcholine (dpPC) and a poly(ethylene glycol) (PEGn) derivative of dipalmitoylphosphatidylethanolamine (PE) (where n = 350, 1000, and 5000, respectively, refer to PEG molecular masses) were submitted to 1H spin–lattice relaxation time (T1) and 31P NMR spectra analysis. 1H NMR relaxation times revealed two contributing components in each proton system (PEG, phospholipids, and water), for all the mixtures studied, exhibiting values of T1 with very different orders of magnitude. This allowed identifying confined and bulk water populations as well as PEG moieties becoming more disordered and independent from the phospholipid moiety as n increased. 31P spectra showed a typical broad bilayer signal for n = 350 and 1000, and an isotropic signal characteristic of micelles for n = 5000. Surface pressure (π)–molecular area isotherms and compressional modulus measurements provided further structural information. Moreover, epifluorescence microscopy data from monolayers at π ∼ 30 mN/m, the expected equilibrium π in lipid bilayers, allowed us to postulate that both 1H populations resolved through NMR in phospholipids and lipopolymers corresponded to different phase domains.